2022
DOI: 10.12968/bjon.2022.31.8.s24
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nurses' knowledge and clinical practice in managing local IV complications following an education intervention

Abstract: Background: Peripheral venous catheters (PVCs) are the most common invasive route for the rapid administration of medication and fluids. The care of PVC sites after cannulation can pose challenges depending on nurses' level of knowledge and practice. Aim: To transfer nurses' knowledge into practice on preventing common local complications of intravenous (IV) therapy. Design: A quasi-experimental study was undertaken. Methods: A convenience sample of nurses from surgical and medical wards of a university hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…As for the research areas, Nursing was found in third place (201 documents), behind areas such as General Internal Medicine (372 documents), and Cardiovascular System Cardiology (279 documents). The competence of placement of a venous catheter varied as a function of the type of catheter, but monitoring and follow-up were nursing responsibilities [30][31][32]. Different studies [30][31][32][33] corroborate the benefits obtained from continuous education based on evidence and adherence to good practices guides and protocols.…”
Section: Bibliometric Elements Of the Scientific Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…As for the research areas, Nursing was found in third place (201 documents), behind areas such as General Internal Medicine (372 documents), and Cardiovascular System Cardiology (279 documents). The competence of placement of a venous catheter varied as a function of the type of catheter, but monitoring and follow-up were nursing responsibilities [30][31][32]. Different studies [30][31][32][33] corroborate the benefits obtained from continuous education based on evidence and adherence to good practices guides and protocols.…”
Section: Bibliometric Elements Of the Scientific Productionmentioning
confidence: 95%
“…The competence of placement of a venous catheter varied as a function of the type of catheter, but monitoring and follow-up were nursing responsibilities [30][31][32]. Different studies [30][31][32][33] corroborate the benefits obtained from continuous education based on evidence and adherence to good practices guides and protocols. Therefore, evidence-based standards such as those published in the document Infusion Therapy Standards of Practice in 2021 of the Infusion Nurses Society (INS) [34] should be a priority in their clinical use by professionals.…”
Section: Bibliometric Elements Of the Scientific Productionmentioning
confidence: 95%
“…The interaction between theory, training, and research needs to be continual, reciprocal, and cyclical to support the nursing profession's capacity to fulfill societal commitments. This will encourage theory-guided practice and aid in bridging the perceived "gap" between theory and practice [5].…”
mentioning
confidence: 99%